The Hummoral Immune Response of Heat Stressed Broiler Chicks Fed Different Levels of Energy and Methionine - Elagib, Hind A.A.; Elzubeir, E.A. (International Journal of Poultry Science, 2012)
The present study was conducted to investigate the effect of feeding different levels of energy and methionine on the total antibody, IgG, IgM immunoglobulin titer of broiler chicks. Thirty chicks were reared in an open sided house with temperature range from 29-42°C. The birds were divided into six groups of five replicate with individual bird. Six experimental diets were used with two levels of energy 3050, 2850 kcal/kg and three levels of methionine: control (0%, 0.2% and 0.4%) above the recommended level. At 14 day of age the birds were immunized with 0.2% Sheep Red Blood Cell (SRBC) suspension. The total antibody titer against SRBC was evaluated at 5 and 10 days post immunization using haemagglutination test. 0.1M 2-meracaptoethanol was used to determine IgG, IgM immunoglobulin. The total antibody titer response to SRBC was significantly (p<0.05) increased in birds fed 0.2 and 0.4% methionine supplemented diets. The different levels of energy 3050 kcal/kg and 2850 kcal/kg had no significant (p>0.05) effect on total antibody titer. At 5 and 10 days post immunization IgG increased significantly (p<0.05) with 0.2 and 0.4% methionine above the recommended level. However, no change was observed in the titer of lgM. The different levels of energy had no effect on IgG and IgM titer.